Role for Occupational Therapy in Community Mental Health: Using Policy to Advance Scholarship of Practice. Issue 4 (2nd October 2015) - Mahaffey, Lisa; Burson, Kathrine A.; Januszewski, Celeste; Pitts, Deborah B.; Preissner, Katharine
ABSTRACT: Occupational therapists must be aware of professional and policy trends. More importantly, occupational therapists must be involved in efforts to influence policy both for the profession and for the people they serve (Bonder, 1987). Using the state of Illinois as an example, this article reviews the policies and initiatives that impact service decisions for persons with psychiatric disabilities as well as the rationale for including occupational therapy in community mental health service provision. Despite challenges in building a workforce of occupational therapists in the mental health system, this article makes the argument that the current climate of emerging policy and litigation combined with the supporting evidence provides the impetus to strengthen mental health as a primary area of practice. Implications for scholarship of practice related to occupational therapy services in community mental health programs for individuals with psychiatric disability are discussed.